Cost of production of food crops: St. Catherine - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Ciencias Agrícolas (IICA), 2021)
The data presented in this publication consist of an update of the cost of production information released in July 1991. The technical coefficients for the different labour operations and inputs have been converted to metric units per hectare. The cost and returns were estimated using 1994 prices.